Bottom Trawling and Multi‐Marker eDNA Metabarcoding Surveys Reveal Highly Diverse Vertebrate and Crustacean Communities: A Case Study in an Urbanized Subtropical Estuary - Jack Chi‐Ho Ip; Hai‐Xin Loke; Sam King Fung Yiu; Meihong Zhao; Yixuan Li; Yitao Lin; Chun‐Ming How; Jiezhang Mo; Meng Yan; Jinping Cheng; Vincent Chi‐Sing Lai; Leo Lai Chan; et al. (Environmental DNA)
ABSTRACT Estuarine habitats serve as critical feeding and nursery grounds for many aquatic species and support fisheries. However, monitoring these complex ecosystems using conventional trawling methods is destructive, costly, and labor‐intensive. This study compared trawling and a multi‐marker environmental DNA (eDNA) metabarcoding approach to monitor marine vertebrate and crustacean communities in an estuarine environment in subtropical Hong Kong. We analyzed 16 bottom trawl samples and the eDNA from 32 two‐liter water samples using primer sets specific to fishes and mammals (MiFish‐U, 12S‐V5, and Berry‐Fish) and decapod crustaceans (MiDeca). We found that the eDNA approach detected more pelagic and demersal fishes (237 vs. 106 in trawling) and elasmobranchs (6 vs. 3) than trawling. The eDNA approach was also more effective than trawling in detecting threatened vertebrates (16 vs. 4), including the Indo‐Pacific Finless Porpoise and the critically endangered Large Yellow Croaker. Among the detected fish at species level, 70 species were detected by both approaches, 32 species were detected by trawling only, and 142 species were detected by the eDNA approach only. Regarding crustaceans, the eDNA approach detected slightly fewer decapods (61 vs. 77) and stomatopods (5 vs. 8) than trawl surveys. However, the eDNA approach could be enhanced through the development of suitable decapod‐specific primers and the expansion of the local reference database. In addition, multivariate analyses of the eDNA data revealed spatial patterns of fish and crustacean assemblages that might be associated with sediment loading, oxygen, and nutrient levels. Furthermore, there was a positive correlation between eDNA read counts and trawl catch, but their correlation coefficient was low. We conclude that eDNA metabarcoding can provide high‐resolution detection of species, composition, and unravel community–environment relationships in estuarine ecosystems. Overall, integrating the non‐destructive eDNA approach can complement the conventional trawling method for better‐informed sustainable fishery management and conservation.